Sleep patterns and risk of new-onset hypertension and cardiovascular disease in prehypertensive adults: The UK Biobank Study - Wanqing Yan; Menglin Fan; Jin Lv; Shaoyong Xu; Yong Ren (Preventive Medicine Reports, 2025)
Objective: This study aimed to investigate the relationship between comprehensive sleep patterns and the incidence of new-onset hypertension (HTN) and cardiovascular disease (CVD) in individuals with prehypertension. Methods: This analysis included 118,523 baseline participants from the UK Biobank (2006–2010) with follow-up through 31 December 2021. A sleep pattern included chronotype, sleep duration, insomnia, snoring, and excessive daytime sleepiness. Cox proportional hazards regression models were used to estimate hazard ratios (HRs) and 95 % confidence intervals (CIs). Results: Over a median follow-up period of 12.5 years, 10,276 participants (8.7 %) developed HTN, and 7665 participants (6.5 %) experienced CVD events. Participants adhering to healthy sleep patterns had a 27 % lower risk of developing HTN (HR = 0.73; 95 % CI: 0.69–0.77) and a 23 % lower risk of CVD (HR = 0.77; 95 % CI: 0.72–0.82) compared with those with unhealthy sleep patterns. When analyzed as a continuous variable, higher healthy sleep scores were associated with a progressive reduction in disease risks. Conclusions: Healthy sleep patterns are significantly associated with reduced risk the risk of new-onset HTN and CVD in people with prehypertension, emphasizing the importance of assessing and optimizing sleep health as part of clinical primary prevention strategies for CVD in prehypertensive populations.